1997
DOI: 10.1038/sj.cdd.4400278
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled apoptosis during acute inflammatory lung injury

Abstract: Apoptosis is a mode of cell death currently thought to occur in the absence of inflammation. In contrast, inflammation follows unscheduled events such as acute tissue injury which results in necrosis, not apoptosis. We examined the relevance of this paradigm in three distinct models of acute lung injury; hyperoxia, oleic acid, and bacterial pneumonia. In every case, it was found that apoptosis is actually a prominent component of the acute and inflammatory phase of injury. Moreover, using strains of mice that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 16 publications
3
45
1
Order By: Relevance
“…ROS can cause oxidation and inactivation of a variety of macromolecules in the lung including proteins, lipids and DNA [19][20]. Several studies of cells in culture have shown that cells are injured by the detrimental effects of hyperoxia [21][22][23][24][25][26]. In addition, animal models and human trials have demonstrated that exposure to prolonged hyperoxia is associated with the development of acute lung injury and the progression to chronic lung disease [1].…”
Section: Discussionmentioning
confidence: 99%
“…ROS can cause oxidation and inactivation of a variety of macromolecules in the lung including proteins, lipids and DNA [19][20]. Several studies of cells in culture have shown that cells are injured by the detrimental effects of hyperoxia [21][22][23][24][25][26]. In addition, animal models and human trials have demonstrated that exposure to prolonged hyperoxia is associated with the development of acute lung injury and the progression to chronic lung disease [1].…”
Section: Discussionmentioning
confidence: 99%
“…In the mid-1990s, with the increased understanding of apoptosis and the available molecular approaches, we and others addressed the question of whether lung epithelium undergoes programmed cell death in hyperoxic lungs [32,34]. These studies reveal that apoptosis of epithelial cells occurs in hyperoxic lungs.…”
Section: Pulmonary Epithelial Cell Death In Hyperoxiamentioning
confidence: 99%
“…Caspase activation is considered to represent the onset of irreversible apoptotic pathway. Caspase-1, an important mediator in both apoptosis and inflammation, is activated in fractionated lysates of hyperoxic mouse lungs [34]. Exposure of caspase-3 deficient mice to hyperoxia for 72 hours induced less apoptotic cell death of lung epithelial cells, compared to that of the wildtype mice [12].…”
Section: Pulmonary Epithelial Cell Death In Hyperoxiamentioning
confidence: 99%
“…Male C57BL/6 mice (6-8 weeks), purchased from Jackson Laboratories (Bar Harbor, Maine), were exposed to >99 or 65% for 72 h as described O 2 previously and then sacrificed [7]. The lungs were lavaged with 2 separate 1-ml aliquots of sterile saline.…”
Section: Exposure To Hyperoxia In Vivo and Isolation Of Alveolar Macrmentioning
confidence: 99%
“…The inhalation of supraphysiological oxygen concentrations for prolonged or even transient periods of time results in acute lung injury, which is characterized by the injury and death of pulmonary cells [6][7][8][9][10][11]. The role of hyperoxia as a potential cause of lung cell injury has been extensively characterized in alveolar epithelial [12][13][14][15][16][17] and endothelial cells [18,19].…”
Section: Introductionmentioning
confidence: 99%